1972
DOI: 10.1346/ccmn.1972.0200604
|View full text |Cite
|
Sign up to set email alerts
|

The Stability of Gibbsite and Boehmite at the Surface of the Earth

Abstract: Abstract--Two mutually exclusive views exist concerning the relative stabilities of gibbsite and boehmite in soils. These are examined in terms of experimental and thermodynamic evidence and it is shown that all three possible divariant assemblages of two phases that can exist between gibbsite, beohmite and H20, may do so at 25~ and 1 atmosphere total pressure depending on the status of HeO. It is further shown that the conditions of H20 chemical potential needed to stabilize boehmite + H~O relative to gibbsit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
2

Year Published

1975
1975
2008
2008

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 6 publications
1
19
2
Order By: Relevance
“…Data fiom the Hanford waste tanks (Table F.3) indicate that boehmite (E-AlOOH) is the dominant Al-bearing solid phase in many of the tanks that have high ionic strength conditions, thus conforming with experimental observations of Hsu (1977) and Chesworth (1972). In waste tanks (U-110, C-109, C-112, AW-105, and SY-102) in which aluminum hydroxide or aluminum silicate phases coexist with boehmite, it likely that all these phases are at equilibrium, or phase conversion may be occuring indicating disequilibrium conditions.…”
Section: F2 Aluminum-containing Solid Phasessupporting
confidence: 78%
See 1 more Smart Citation
“…Data fiom the Hanford waste tanks (Table F.3) indicate that boehmite (E-AlOOH) is the dominant Al-bearing solid phase in many of the tanks that have high ionic strength conditions, thus conforming with experimental observations of Hsu (1977) and Chesworth (1972). In waste tanks (U-110, C-109, C-112, AW-105, and SY-102) in which aluminum hydroxide or aluminum silicate phases coexist with boehmite, it likely that all these phases are at equilibrium, or phase conversion may be occuring indicating disequilibrium conditions.…”
Section: F2 Aluminum-containing Solid Phasessupporting
confidence: 78%
“…Precipitation experiments conducted by Barnhisel and Rich (1965) and Hsu (1966) Chesworth (1972) showed that neutralization of Al-containing high ionic strength solutions result in the formation of boehmite-like (pseudoboehmite) precipitates. Presence of carboxylic acids also promotes the formation of pseudoboehmite (Kodama and Schnitzer 1980;Violante and Violante 1980;Kwong and Huang 1981;Violante and Huang 1985).…”
Section: F2 Aluminum-containing Solid Phasesmentioning
confidence: 99%
“…However bayerite and nordstrandite crystallize rapidly under extreme alkaline conditions, but gibbsite has a tendency to form in acid solutions (Schoen and Roberson 1970;Barnhisel and Rich 1965;Hsu 1989). In addition, gibbsite has great stability relative to boehmite in the system of A1203-HzO at 25 ~ and 1 atm (Chesworth 1972). These facts suggest that the gibbsite that appeared in the present weathering products must be transformed from the amorphous aluminum hydroxide.…”
Section: Resultsmentioning
confidence: 75%
“…It is important to evaluate these arguments, because they imply the existence of large errors in current experimental and thermodynamic data for the aluminum hydroxides. Chesworth (1972Chesworth ( , 1975Chesworth ( , 1980aChesworth ( , 1980b presented several phase diagrams showing boehmite and gibbsite to be stable at STP without considering the possibility that diaspore is more stable. Thermodynamic and experimental data, however, show that gibbsite, boehmite, and bayerite are always metastable relative to diaspore and water at STP and that boehmite is metastable relative to diaspore at STP even if the uncertainties in the thermodynamic data are considered (Table 3).…”
Section: Metastability Of Boehmite Gibbsite Bayerite and Nordstranmentioning
confidence: 99%